A nationwide analysis of successful litigation claims in neurological practice. (26th February 2014) - Coysh, Thomas; Breen, David P
Objectives: Neurological practice has previously been highlighted as a high-risk speciality with regard to malpractice claims. We set out to study the nature of these claims in order to inform physicians about hazardous areas within their speciality and potentially alter clinical practice. Design: Nationwide retrospective analysis of successful neurology and neurosurgery claims over a 17-year period. Setting: We studied all successful claims occurring between 1995 and 2012 using the NHS Litigation Authority database, which collects data on claims made against clinicians practising in England and Wales. Participants: Four hundred and twenty-three successful claims were identified during the study period. Main outcome measures: The errors involved, the patient groups affected, the resulting mortality and the litigation payments. Results: 63.1% of claims were due to negligence in neurosurgical care, whilst 36.9% were due to negligence in neurological care. Litigation payments were significantly higher in neurosurgery compared to neurology cases. Diagnostic error was the most common cause of litigation. The disease categories with the highest numbers of successful litigation claims were spinal pathology, cerebrovascular disease including subarachnoid haemorrhage, intracranial tumours, hydrocephalus and neuropathy/neuromuscular disease. Conclusions: This is the first study of successful litigation claims against the NHS for negligent neurological or neurosurgical care and provides data to help reduce risk and improve patient safety.